Effects of dietary black cumin seed meal on growth performance, meat quality, rumen and blood parameters in lambs - Toker, Osman; Konca, Yusuf; Sahin, Ahmet (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study was conducted to investigate the effects of dietary black cumin seed meal on growth performance, meat quality, rumen and blood parameters in lambs. A total of 32 Akkaraman male lambs aged 3 months were allocated individual pens with 8 replicates and fed with experimental diets for 84 days. Experimental groups were as follows: 1: Control (C, no black cumin seed meal, BCSM), 2: BCSM supplementation to concentrate 5% (BCSM5), 3: BCSM supplementation to concentrate 10% (BCSM10), and 4: BCSM supplementation to diets 20% (BCSM20). Although dietary BCSM did not affect growth performance, blood parameters, carcass, and meat traits, BCSM increased meat cooking loss (at 5% level) and meat thawing loss (at 10 % level) compared to control and other treatments (P<0.05). BCSM also did not change rumen volatile fatty acids, except decrease in butyric acids on the 35th day of the experiment. In conclusion, when given the optimal energy: protein ratio, black cumin seed meal can be used as an alternative protein source in animal feeds since it does not negatively affect the growth performance, carcass quality and health status of lambs.